Oriented arrangement of simple monomers enabled by confinement: towards living supramolecular polymerization - Yingtong Zong (Nature Portfolio, 2021)
Using simple monomers in living supramolecular polymerization is difficult due to energy principles. Here the authors use confinement from a layered double hydroxide nanomaterial to successfully polymerise several simple monomers with length control and narrow dispersity.